2013
DOI: 10.1007/s11187-013-9482-z
|View full text |Cite
|
Sign up to set email alerts
|

How Swiss small and medium-sized firms assess the performance impact of mergers and acquisitions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Moreover, companies achieve a higher specialization when they have accumulated knowledge through internal development, whereas previous R&D outsourcing and M&As lead to diversification. Such results are consistent with previous research (Arvanitis and Stucki, 2014; Hoberg and Phillips, 2010; Teirlinck and Spithoven, 2013).…”
Section: Data Analysis and Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, companies achieve a higher specialization when they have accumulated knowledge through internal development, whereas previous R&D outsourcing and M&As lead to diversification. Such results are consistent with previous research (Arvanitis and Stucki, 2014; Hoberg and Phillips, 2010; Teirlinck and Spithoven, 2013).…”
Section: Data Analysis and Resultssupporting
confidence: 94%
“…Mergers between firms with similar product markets are associated with larger positive effects than diversifying mergers (Ahuja and Katila, 2001; Arvanitis and Stucki, 2014; Bena and Li, 2014; Fan and Goyal, 2006). Companies merge with partners with technological proximity or complementary assets that expand their range of products through new products introductions (Hoberg and Phillips, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Arvanitis and Stucki [45] analyzed the impact of M&As on the economic performance of SMEs. The authors suggested five groups of motives: growth (increase market share, broaden the product mix, entry into new business), cost (spread fixed costs, rationalization of procurement/production/marketing and sales), resources (obtain access to specific know-how/network), risks (spread the market risk), and innovation (reduce costs of R&D, obtain access to innovation-related know-how/networks, reduce the risk of the R&D portfolio/of being imitated).…”
Section: Relationship Between Manda and Promising Areasmentioning
confidence: 99%
“…Cost reduction includes the reduction of average or marginal costs of production, fixed costs, financial costs and R&D costs [44,45]. Keywords related to cost reduction can ultimately lead to "growth" and "innovation" as companies can have the same or higher output compared to smaller input by achieving higher efficiency and productivity within the enterprise.…”
Section: Relationship Between Manda and Promising Areasmentioning
confidence: 99%